Process Engineering App lied to the Production of Bioethanol Using Banana Rejection Urabá - Daniel Flórez Alvarado; Adriana Lara Sandoval (Publicaciones e Investigación, 2012)
Most countries either financially or in advanced stages of development are faced with the problem of disposal and treatment of waste and organic waste; these can be treated in different ways, for example by reducing its volume or processing any useful substance using physicochemical transformation processes bananas in bioethanol and analyzing environmental impacts to meet sanitary standards. The objective of this study was to evaluate the potential for ethanol production from banana and the study and application of process engineering in ethanol production using banana rejection as feedstock in the region of Urabá. Bioethanol is obtained by fermentation and distillation of rejected bananas where the results are reflected in the operational controls and leaf pattern obtained in the standardization process.